Uncovering the gaps in managed aquifer recharge for sustainable groundwater management: A focus on hillslopes and mountains - Meles, Menberu B.; Bradford, Scott; Casillas-Trasvina, Alberto; Chen, Lin; Osterman, Gordon; Hatch, Tyler; Ajami, Hoori; Crompton, Octavia; Levers, Lucia; Kisekka, Isaya (Journal of hydrology (Amsterdam), 2024)
•Managed Aquifer Recharge (MAR) enhances aquifers replenishment and water resilience.•Existing MAR tech suits flat terrains but faces several unknowns and limitations.•Exploring new MAR methods viability is crucial for sustainable groundwater future.•Hillslope, mountain front, and road MAR offer fast recharge and better water quality.•Expanding MAR to hillslope and road needs modifying landscape and extensive research. Managed Aquifer Recharge (MAR) is a promising approach to enhance water supply resilience, but it faces significant challenges, such as limited space and time for recharge activities, as well as uncertain bio-geophysical processes, and complex subsurface flow and heterogeneity. In this review, we assess the viability of hydrology-based approaches to enhance groundwater replenishment and identify missing components in existing groundwater recovery activities. We discuss expanding recharge opportunities to under-utilized sources and locations such as hillslopes and mountain systems. Additionally, we explore the possibilities of using existing road infrastructure to capture runoff and convey it to secondary porosity (alluvial fans, faults and fractures) in the mountain fronts. Conventional MAR approaches are usually implemented on valley floors where restrictive clay layers can impede recharge to deep aquifers, and the presence of legacy contaminants in the root or vadose zones can degrade water quality. Hillslope and mountain recharge strategies offer multiple potential benefits over valley floors when there is improved connectivity and faster recharge to deep aquifers, shallower vadose zones, coarser textured deposits, and better surface water quality. Studies show that hillslope recharge accounts for 15–50% of the recharge to valley floors. To further facilitate the effective expansion of groundwater recharge, we propose landscape modifications encompassing slope correction and implementing biological and structural techniques to repurpose roadside channel systems to slow down and/or store flow in hillslopes. These systems can facilitate groundwater recharge and ultimately contribute to sustainable groundwater management. Innovative scientific analyses can help us understand the impacts of MAR on water quality and quantity, uncover the limitations and strengths of recharge in specific locations, and identify the most effective systems. Addressing these gaps will help us achieve a more resilient and sustainable groundwater future.